Reducing body dissatisfaction by means of an evaluative conditioning procedure in undergraduate women: A replication study. (October 2019) - Glashouwer, Klaske A.; Masselman, Irina; de Jong, Peter J.
Abstract: The aim was to investigate whether a computer-based evaluative conditioning (EC) procedure using positive social feedback is effective in enhancing body satisfaction. Prior findings in three small-scale studies were mixed showing positive effects in pre-clinical samples, but not in a clinical sample of eating disorder patients. Therefore, our main goal was to replicate the original finding of Martijn et al. (2010) in a well-powered unselected sample of 129 female undergraduates. We assessed the impact of EC on questionnaire measures of body satisfaction as well as on affective ratings of the participants' body pictures used in the task to verify whether the EC procedure was effective in heightening the subjective valence of these pictures. Supporting the validity of the current EC procedure, participants in the experimental condition rated their own pictures after the training as more positive than participants in the control condition. However, this effect of the EC procedure did not transfer to the self-report indices of body satisfaction. In addition, women with relatively high body concern did not profit more from the EC procedure than women with relatively low body concern. Together, these findings suggest that the EC procedure in its present form is not ready for use as an intervention for improving body satisfaction. However, it seems worthwhile to investigate in future studies how the EC procedure can be further strengthened in a way that effects on stimulus ratings eventually also 'spill over' to the level of self-reported body satisfaction. Highlights: The evaluative conditioning procedure improved ratings of own body pictures. The conditioning effect was similar for women with high vs. low body concern. The conditioning effect did not transfer to self-report indices of body satisfaction. This evaluative conditioning procedure is not ready for being used in treatment.